2022
DOI: 10.3390/nano12060999
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Carbon Dioxide into Methanol Using Cu–Zn Nanostructured Materials as Catalysts

Abstract: Nowadays, there is a growing awareness of the great environmental impact caused by the enormous amounts of carbon dioxide emitted. Several alternatives exist to solve this problem, and one of them is the hydrogenation of carbon dioxide into methanol by using nanomaterials as catalysts. The aim of this alternative is to produce a value-added chemical, such as methanol, which is a cheaply available feedstock. The development of improved materials for this conversion reaction and a deeper study of the existing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
(52 reference statements)
3
12
0
Order By: Relevance
“…However, the use of porous supports is beneficial for the methanol synthesis. This is in agreement with the literature, where it has been demonstrated that the presence of porous materials improves CO 2 adsorption and the distribution of the active sites [9].…”
Section: Resultssupporting
confidence: 93%
“…However, the use of porous supports is beneficial for the methanol synthesis. This is in agreement with the literature, where it has been demonstrated that the presence of porous materials improves CO 2 adsorption and the distribution of the active sites [9].…”
Section: Resultssupporting
confidence: 93%
“…According to the report of Horbatenko, the synthesis of DPG from PO and PG is an exothermic reaction (Δ H = −49.39 kJ·mol –1 ). Therefore, the low temperature (<140 °C) is beneficial for the PO and PG reactions . As the loading of WO 3 increased from 0 to 35 wt %, the conversion of PO on x WO 3 /20ZrO 2 –Hβ was almost unchanged at reaction temperatures below 140 °C, and the conversion of PO on x WO 3 /20ZrO 2 –Hβ increased slightly at high temperatures (>140 °C).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, it can also be applied as a fuel to form many other liquid hydrocarbon fuels and methanol, creating it economically feasible. 165,166 CO does not cause climate change directly, although its presence can affect the abundance of greenhouse gases such as CH 4 and CO.…”
Section: Electrochemical Co 2 Reductionmentioning
confidence: 99%